Efficiency of PFC Operating in Spread Spectrum Mode for EMI Reduction - Jankovskis, J.; Stepins, D.; Pikulins, D. (Elektronika ir Elektrotechnika, 2010)
The investigation deals with the influence of spread spectrum technology (SST) on several of the most important power quality parameters of switch–mode power factor corrector. The analysis covers some significant effects of frequency dependence of power losses, specific for the power components. Computer simulations and experimental results show the most distinguishing dependences of different power quality parameters on SST. The provided data allow to conclude that the implementation of frequency modulation in power factor corrector does not worsen the total harmonic distortion, the efficiency and the power factor in the wide range of modulating frequencies, deviation values and output power variation. Thus SST is one of the most promising methods for EMI reduction in power factor correctors. Ill. 7, bibl. 14 (in English; abstracts in English, Russian and Lithuanian)